Mitochondrial Delivery of Phenol Substructure Triggers Mitochondrial Depolarization and Apoptosis of Cancer Cells - Gazzano, Elena; Lazzarato, Loretta; Rolando, Barbara; Kopecka, Joanna; Guglielmo, Stefano; Costamagna, Costanzo; Chegaev, Konstantin; Riganti, Chiara (Frontiers in Pharmacology, 2018)
Antitumor chemotherapy remains one of the most important challenge of the medicinal chemistry. Emerging research in chemotherapy is focused on exploiting the biochemical differences between cancer cell and normal cell metabolism in order to reduce the side effects and increase antitumor therapy efficacy. The higher mitochondrial transmembrane potential of cancer cells compared to not-transformed cells favors the intra-mitochondrial accumulation of cationic drugs in the former. This feature could be exploited to allow selective delivery of antineoplastic drugs to the cancer cells. In this work we designed and synthetized phenol derivatives joined to the triphenylphosphonium (TPP) cation, a well-known vector for mitochondrial targeting. Two designed phenol TPP-derivatives 1 and 2 show remarkable cytotoxic activity against different cancer cell lines, but were less toxic against normal cells. The differential cytotoxicity relied on the higher mitochondrial biogenesis and oxidative-phosphorylation metabolism of the former. By reducing mitochondrial mass and energetic metabolism, and increasing at the same time the levels of intra-mitochondrial reactive oxygen species, phenol TPP-derivatives 1 and 2 induced mitochondria depolarization and triggered a caspase 9/3-mediated apoptosis, limited to cancer cells. This work provides the rationale to further develop phenol TPP-derivatives targeting mitochondrial as new and selective anticancer tools.